Factors affecting halal food purchase intention in Kuantan, Pahang / Siti Zaleha Wahab Abu Jalil - Wahab Abu Jalil, Siti Zaleha (2018)
According to the Department of Statistics Malaysia, percentage for the Muslim in Malaysia are the largest which are up to 6 1 .3% compared to other religion which is took more than half of the population in Malaysia country. Meanwhile for Buddhism 19.8%, Christianity 9.2% and lastly Hinduism 6.3. Nevertheless, Malaysia is one of the country that have large and growing food retail market supplied by local and imported products. This study will focus on the aspects and reasoning that affect Halal food purchase intention among Muslim people in Kuantan, Pahang. The data is collected within one month through the survey approach. The respondent chosen are 190 people to answer the questionnaire that using the technique of Likert Scale. The data receive is analysed the descriptive and multiple regression analysis by using the SPSS Statistics VV22.0 program. The dependent variables for this study is intention to purchase Halal food products. Meanwhile, for the independent variables are Halal awareness, personal societal perception, Halal marketing, Halal certification and religious belief. The findings for this study is there is significant relationship between the dependent and independent variable. This study can be a new guideline to the entrepreneur before their emerging into the food market segment in the future.